Designing a backstepping sliding mode controller for an assistant human knee exoskeleton based on nonlinear disturbance observer. (October 2018) - Khamar, M.; Edrisi, M.
Abstract: In present study, a knee exoskeleton was designed to assist human movements in the flexion/extension of the knee. Moreover, a control method was proposed for the exoskeleton to track the desired position trajectory of the knee. Subsequently, an integrated human shank and exoskeleton model based on the sitting position was considered. A nonlinear disturbance observer (NDO) was used to reduce the influence of the uncertainties and external disturbance in modeling of the whole system. Furthermore, a backstepping sliding control (BSC) approach combined with the nonlinear observer was presented. To improve performance of BSC, genetic algorithm (GA) was employed to determine the optimal backstepping sliding control law parameters. The asymptotic stability of the presented controller and nonlinear disturbance observer convergence were mathematically verified based on the Lyapunov theory. The superiority of the proposed control method is shown in comparison to some recent new methods. The suggested controller can reduce the disturbance rejection time. The chattering and tracking error of NDO sliding mode control was also reduced. The proposed controller was simulated in MATLAB (a registered trademarks of The MathWorks, Inc.) and OpenSim was used to model the human knee. Moreover, some experimental results verified the designed system and its simulation and illustrated that the backstepping sliding mode controller based on the nonlinear disturbance observer can track the reference position by considering a nonlinear model of the identification errors and the external disturbances.